Leveraging meaning-induced neural dynamics to detect covert cognition via EEG during natural language listening—a case series - Alkhoury, Ludvik; O'Sullivan, James; Scanavini, Giacomo; Dou, Jin; Arora, Joshitha; Hamill, Lilah; Patchell, Abigail; Radanovic, Ana; Watson, William D.; Lalor, Edmund C.; Schiff, Nicholas D.; Hill, N. Jeremy; et al. (Frontiers in Psychology, 2025)
At least a quarter of adult patients with severe brain injury in a disorder of consciousness may have cognitive abilities that are hidden due to motor impairment. In this case series, we developed a tool that extracted acoustic and semantic processing biomarkers from electroencephalography recorded while participants listened to a story. We tested our method on two male adolescent survivors of severe brain injury and showed evidence of acoustic and semantic processing. Our method identifies cognitive processing while obviating demands on attention, memory, and executive function. This lays a foundation for graded assessments of cognition recovery across the spectrum of covert cognition.